A Systematic Review on Non-Performing Assets in Banks in India - et. al., Aniket Pundir , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Lending is a cruttial part of financial sector that is Banks/NBFCs in India. It is main revenue génération business of Bank/NBFCs. Financial Institution i.e. Bank and NBFCs used to borrow funds from the market i.e. from other institution & public and then lend the same again to its clients to gain profits to its owners/investors. There were 27 Public Sector Banks in India (Incl. SBI Associates Banks) before announcement of merger of some Banks by Union Govt. Of India in the year 2019 and there are multiple other Pvt. Sector Banks and NBFCs, co-operative bank and regional rurul bank which we studied in this paper. Lending business of the Banks/NBFCs is facing slowdown in recent years. Non-Performing Assets are increasing day by day which is creating big problem not only to financial sector i.e. Bank/NBFCs but also for other industries. In this paper we will systemtically review the literature/artiles already pubilshed on NPAs in India and to know the main reasons and factor which are resposible for rising NPA in financial institutions and to find out scope of further research on this topic.